Occurrence of Organophosphorus Flame Retardants and Plasticizers (PFRs) in Belgian Foodstuffs and Estimation of the Dietary Exposure of the Adult Population - Poma, Giulia; Sales, Carlos; Bruyland, Bram; Christia, Christina; Goscinny, Séverine; Van Loco, Joris; Covaci, Adrian (Environmental science & technology, 2018)
The occurrence of 14 organophosphorus flame retardants and plasticizers (PFRs) was investigated in 165 composite food samples purchased from the Belgian market and divided into 14 food categories, including fish, crustaceans, mussels, meat, milk, cheese, dessert, food for infants, fats and oils, grains, eggs, potatoes and derived products, other food (stocks), and vegetables. Seven PFRs [namely, tri-n-butyl phosphate (TnBP), tris(2-chloroethyl) phosphate (TCEP), tris(1-chloro-2-propyl) phosphate (TCIPP), tris(1,3-dichloro-2-propyl) phosphate (TDCIPP), triphenyl phosphate (TPHP), 2-ethylhexyldiphenyl phosphate (EHDPHP), and tris(2-ethylhexyl) phosphate (TEHP)] were detected at concentrations above quantification limits. Fats and oils were the most contaminated category, with a total PFR concentration of 84.4 ng/g of wet weight (ww), followed by grains (36.9 ng/g of ww) and cheese (20.1 ng/g of ww). Our results support the hypothesis that PFR contamination may occur during industrial processing and manipulation of food products (e.g., packaging, canning, drying, etc.). Considering the daily average intake of food for the modal adult Belgian (15-64 years of age), the dietary exposure to sum PFRs was estimated to be ≤7500 ± 1550 ng/day [103 ± 21 ng/kg of body weight (bw)/day]. For individual PFRs, TPHP contributed on average 3400 ng/day (46.6 ng/kg of bw/day), TCIPP 1350 ng/day (18.5 ng/kg of bw/day), and EHDPHP 1090 ng/day (15 ng/kg of bw/day), values that were lower than their corresponding health-based reference doses. The mean dietary exposure mainly originated from grains (39%), followed by fats and oils (21%) and dairy products (20%). No significant differences between the intakes of adult men and women were observed.